The Gerbode defect: a case series. Issue 2 (12th January 2021) - Sunderland, Nicholas; El-Medany, Ahmed; Temporal, Justin; Pannell, Laura; Doolub, Gemina; Nelson, Martin; Vohra, Hunaid
Abstract: Background : The Gerbode defect is a rare abnormal communication between the left ventricle (LV) and right atrium (RA). The lesion is either congenital or acquired. Acquired defects are largely iatrogenic or infective in origin. We present two cases of acquired Gerbode defects with similar clinical presentations but very different outcomes. Case summaries: Patient 1 A 64-year-old male presented with features of decompensated cardiac failure and a low-grade temperature. Dehiscence of a recently implanted bioprosthetic aortic valve and high-velocity LV to RA jet (Gerbode defect) was found on echocardiography. Blood cultures grew Staphylococcus warneri and the diagnosis of infective endocarditis was established. The patient was treated with intravenous antibiotics and the aortic valve and Gerbode defect were successfully surgically repaired. Patient 2 An 81-year-old male presented after being found on the floor at home. On admission, he was clinically septic with evidence of decompensated heart failure. No clear infective focus was initially found. Transthoracic echocardiography revealed severe left ventricular impairment, with a normal bioprosthetic aortic valve. He was treated with intravenous antibiotics, but later deteriorated with evidence of embolic phenomena. Repeat echocardiography revealed a complex infective aortic root lesion with bioprosthetic valve dehiscence and flow demonstrated from the LV to RA. Unfortunately, the patient succumbed to the infection and cardiac complications. Discussion : The Gerbode defect is a rare but important complication of infective endocarditis and valve surgery. Care needs to be taken to assess for Gerbode defect shunts on echocardiogram, especially in the context of previous cardiac surgery.